2015
DOI: 10.1007/s11266-015-9618-7
|View full text |Cite
|
Sign up to set email alerts
|

International Aid, Local Ownership, and Survival: Development and Higher Education in Rural Haiti

Abstract: This case study of Rural Haitian University highlights the complexities and consequences that may arise from a combination of unpredictable streams of international funding, financial vulnerability of communities, and the strategies that civic leaders employ to mobilize resources. We argue that the encounter sketched here of local vulnerability following protracted social conflict and a major natural disaster with the international aid machinery has fostered a cycle of dependence/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…They confront similar, or perhaps even more, setbacks when seeking funding for their education and healthcare initiatives in rural Haiti. For example, Zanotti, Stephenson, Jr., and McGehee () reported that after the earthquake, the volatility of donor preferences and priorities was a major barrier to sustaining the initiatives of the Rural Haitian University founded by a local Haitian.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They confront similar, or perhaps even more, setbacks when seeking funding for their education and healthcare initiatives in rural Haiti. For example, Zanotti, Stephenson, Jr., and McGehee () reported that after the earthquake, the volatility of donor preferences and priorities was a major barrier to sustaining the initiatives of the Rural Haitian University founded by a local Haitian.…”
Section: Resultsmentioning
confidence: 99%
“…As noted by Klimovich and Thomas (), the significant impact of the earthquake on the capital led to a massive relief effort that not only brought many NGOs into the country, but also increased the presence of existing NGOs. Several factors exemplify the systemic infrastructural and societal vulnerabilities in Port‐au‐Prince and Haiti as a whole: institutional and governing structures weakened by decades of upheaval and external intervention; large economic disparities between the elite and the poor; a lack of access to healthcare services and educational opportunities outside of the capital; a high level of dependence on foreign aid and remittances from the Haitian diaspora in Canada, France, the United States, and other countries; and repeated disasters accompanied by slow recovery processes (Farmer, ; Schuller and Morales, ; Zanotti, Stephenson, Jr., and McGehee, ). The next section provides additional details about diaspora contributions more generally, and the various means and strategies used to mobilise resources.…”
Section: Research Context: the Earthquake In Haiti In 2010mentioning
confidence: 99%
“…Several authors have detailed the systemic societal, institutional, and infrastructural vulnerabilities in Haiti that have led to a high dependence on foreign aid and the labeling of Haiti as the "republic of NGOs" (Cunningham, 2012;Farmer, 2011;Klarreich & Polman, 2012;Ramachandran & Walz, 2015;Schuller, 2012a;Schuller & Morales, 2012;Zanotti, Stephenson, & McGehee, 2016). Many of these scholars explore a broader assessment of the underlying factors and forces that have led to such lopsided dependence on foreign aid.…”
Section: Case Study Background and Context: The Haiti Earthquakementioning
confidence: 99%
“…Approximately 21 090 individuals receive vocational training in Haiti (Suzuta, 2011), and there is some scholarship and practice-based reporting on the efficacy of such training (Bigelow, 2010;RTI International, 2018). There is limited empirical research on student experiences in the Haitian higher education system (Vital, 2015;Dumay, 2009;Endicott, 2019;Jacob, 2020;Pierre, Arrellano, Ramírez, Gómez, & Romero, 2014;Rameau, Louime, & Behar-Horenstein, 2007;Zanotti, Stephenson, & McGehee, 2016) and even less that specifically examined the university-based career training preparation programmes and trajectory of university students and graduates in Haiti. This research addressed a gap in research on career counselling in the Haitian context.…”
Section: Introductionmentioning
confidence: 99%